ROLE PLAY METHOD ON TUBERCULOSIS PREVENTION BEHAVIOR IN SCHOOL-AGED CHILDREN - I Gusti Ayu Putu Desy Rohana; Saprianto; D. Eka Harsanto; Zanzibar; Eva Luthfiati Putri (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Indonesia is the country with the second highest incidence of TB in the world, and the incidence of treatment interruption has increased after Covid-19. School-age children are at high risk of contracting TB from AFB-positive adults who experience ineffective treatment in the community. This study aims to determine the effect of the role play method on TB transmission prevention behavior in school-age children in Baturaja. This study is a quantitative study using a quasi-experimental design with a control group with a pretest and posttest type. The sample size in this study was 43 students in each intervention and control group. The intervention provided was education with the role play method for 5 training sessions with a therapist in the intervention group, and conventional education in the control group. Data collection using a questionnaire on TB transmission prevention behavior to school-age children. The results of the statistical test obtained a significant increase in the behavior of students in the intervention group with a p value of 0.000 (p <0.05). The results of the study showed a significant effect on the respondents' TB prevention behavior after the role play intervention was carried out. The results of this study are expected to be applied as an alternative method of nursing education for school-age children in improving behavior to prevent TB transmission in the community.